EMI Suppression Characteristics of Pure and Impure Ni-Zn Ferrities and Mg-Zn Ferrities - Ewe, Lay Sheng (2001)
Electromagnetic Interference (EMI) is a wave pollution, which interrupts the functioning of electronic circuits. Therefore, EMI wave absorbing materials are needed to suppress the wave pollution. One of the best solutions to overcome this problem is by using ferrites as EMI suppressors. This work is hoped to give a better understanding on how the purity of constituent oxides affects the suppression capability of ferrites. Moreover. it is also hoped to contribute in understanding how a good EMI suppressor can be made. A total of 1 2 toroidal samples with the composition of NixZnl-xFe204 and another 12 toroidal samples with the composition M&tZnl-xFe204 were prepared via the conventional ceramic processing method, where x = 0.1 , 0. 15, 0.2, 0.25, 0.3, 0.35. These samples were prepared to be ferrites with purities -99.99% and -;!J9. 1% which denoted pure and impure ferrites respectively. Subsequently, these samples were sintered in air at 1300°C. The measured parameters to study the magnetic properties were density, permeability, relative loss factor, impedance, resistivity, microstructure and XRD analysis. It was found that the overall magnetic properties for pure Ni-Zn Ferrites and Mg-Zn Ferrites were only slightly better than those of impure Ni-Zn ferrites and Mg-Zn Ferrites; the parameter values did not differ very much. Therefore, it is more economic if the impure materials are used for ferrite production instead of pure materials, which are more expensive.